2020
DOI: 10.1111/pre.12439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ulva spp. and seasonal disturbances on the recovery of a temperate rocky intertidal community

Abstract: The inhibitory effects of ulvoid algae and their seasonality on the recovery and succession of an intertidal algal community were investigated under field conditions using a two‐factorial design. The experiment was conducted in the mid‐low intertidal zone on the Southern coast of Korea. In spring and fall, each of the ten 50 × 50 cm plots was disturbed artificially, and Ulva spp. were continuously excluded from five plots of the seasonal plots. The succession of spring plots was nearly twice as fast as that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 50 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…It might be because they can alter the availability of resources, competing for space, and preventing recruitment of other later species. A similar pattern of colonization was noted in the studies of Mayakun et al (2010), Mayakun (2019), Mayakun et al (2020), and Yang and Kim (2020). They found that Ulva appeared to inhibit and suppress recruitment by later colonists.…”
Section: Algal Succession Patternssupporting
confidence: 81%
See 4 more Smart Citations
“…It might be because they can alter the availability of resources, competing for space, and preventing recruitment of other later species. A similar pattern of colonization was noted in the studies of Mayakun et al (2010), Mayakun (2019), Mayakun et al (2020), and Yang and Kim (2020). They found that Ulva appeared to inhibit and suppress recruitment by later colonists.…”
Section: Algal Succession Patternssupporting
confidence: 81%
“…(2010), Mayakun (2019), Mayakun et al . (2020), and Yang and Kim (2020). They found that Ulva appeared to inhibit and suppress recruitment by later colonists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations